PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN BATIK SASIRANGAN BORDIR (STUDI KASUS PADA BUNGA BANGKAL SASIRANGAN) - periyadi -; Amalia Wahyuni (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract, The main objective in this research is to review and analyze (1) How much influence the cost of promotion on the sales volume of Bangkal Sasirangan Bunga products. The targets in this study include (1) Increasing the sales volume of Batik Sasirangan Bordir through promotion in accordance with the cost or budget that is owned. (2) Making guidelines for craftsmen or home industry players of Batik Sasirangan Bordir to increase sales volume. This research is a qualitative descriptive study, which will try to find out the relationship between the cost of promotion with the sales volume of Sasirangan Embroidery Batik